Successful case of direct puncture of a prosthetic bypass graft in endovascular treatment for long superficial artery chronic total occlusion: a case report. Issue 6 (24th November 2020) - Sugihara, Makoto; Ueda, Yoko; Yano, Yuiko; Miura, Shin-Ichiro
Abstract: Background: The access site for endovascular therapy (EVT) is often limited because of multi-vascular diseases. Prior lower limb bypass can potentially limit the availability of common femoral artery access when EVT is required. Case summary: An 88-year-old woman who presented with non-healing ulceration in the dorsalis pedis of the left foot despite treatment for several months was admitted to our hospital. She had undergone axillo-bilateral femoral bypass surgery for right critical limb ischaemia 3 years previously. Ultrasound and contrast computed tomography demonstrated bypass graft occlusion, left superficial femoral artery (SFA)-popliteal artery long chronic total occlusion from the origin with severe calcification and severe stenosis in the bilateral common femoral artery close to the anastomotic site. EVT for the left SFA occlusion was necessary to save the left foot, but access sites for EVT were limited. We decided to puncture an occluded axillo-femoral prosthetic bypass graft. It is difficult to cross the wire with only an antegrade approach. Therefore, it was necessary to use a bi-directional approach with dorsalis pedis artery puncture and the Rendez-vous technique. Finally, angiogram demonstrated improved blood flow to the wound site, and haemostasis at the puncture site could be achieved by manual compression. The ulceration healed within a month. Discussion: Direct puncture of a prosthetic bypass graft and additional techniques resulted in complete revascularization. Thus, direct puncture of a bypass graft could be a useful EVT strategy for patients with complex and extremely long chronic total occlusion.